Content validation of an electronic remote toxicity management system in adult patients undergoing cancer treatment: a prospective longitudinal study on the QuestOnco application - Raffaele Longo; Christophe Goetz; Marco Campitiello; Francesca Plastino; Julie Egea; Pierre-Olivier Legros; Arpiné Ardzivian Elnar; Salma Meraihi; Elisabeth Luporsi; Véronique Noirez (BMC Cancer)
Abstract Background Cancer-treatment toxicity is common and symptoms must be identified quickly and accurately. Since symptom reporting during consultations is hampered by time constraints and patient/oncologist biases, patient-reported outcome-measure (PROM) questionnaires are useful. A strong shift to at-home cancer treatment has led to growing interest in remote symptom monitoring via electronic-PROMs (ePROMs). However, because PROMs are generally designed for medical-staff use, ePROMs must be adapted to patient comprehension/abilities. Here, to meet the oncological-healthcare needs of our region, we developed QuestOnco, a mobile-phone ePROM application. It is based on the symptom descriptions and severity grades of the PRO-CTCAE PROM and is designed for real-time on-demand reporting of 34 common or life-threatening cancer-treatment symptoms. This study describes the development of QuestOnco and its content validation relative to two comparators: PRO-CTCAE and the medical records. Methods The cohort study was conducted in a tertiary-care hospital in 2021 and consisted of two stages. Stage I assessed the comprehensibility of QuestOnco for patients: 24 cancer-therapy patients were asked to try the application for 30 min and then underwent semi-structured cognitive interviews. Stage II tested QuestOnco-content validity against the comparators: patients starting a ~ 6-week cancer-therapy cycle were asked to use QuestOnco in an on-demand fashion and to complete weekly paper PRO-CTCAEs. Total QuestOnco, PRO-CTCAE, and medical-record symptom reports were compared in terms of symptom and symptom-severity frequencies. Severity concordance of each reported symptom was assessed by Kendall’s tau-b rank-correlation coefficients. Results In the second round of 12 Stage-I patients (total Stage-I enrollment rate = 100%), 0% reported comprehension difficulties. 110 patients were recruited for Stage II (enrollment rate = 23%). QuestOnco, PRO-CTCAE, and the medical records detected 85%, 100%, and 62% of the target symptoms at least once, respectively, and reported grade-1, -2, -3, and -4 toxicities with similar frequencies (56–67%, 23–32%, 6–10%, and 2–3%, respectively). Overall symptom-severity concordance was moderate with PRO-CTCAE (tau-b = + 0.21, range = -0.03 to + 0.38) and strong with the medical records (tau-b = + 0.33, range = -0.01 to + 0.61). Few remarkable discrepancies were observed. Conclusions The QuestOnco application was well-understood by patients and demonstrated good content validity compared to its parent PROM and the medical records. Trial registration ClinicalTrials.gov No. NCT04915274.